2014
DOI: 10.1111/jocs.12382
|View full text |Cite
|
Sign up to set email alerts
|

Valve Cuspidity: A Risk Factor for Aortic Valve Repair?

Abstract: This study demonstrates no difference in mid-term results after regurgitant bicuspid and tricuspid aortic valve repair, suggesting that bicuspid valve may not be a risk factor for aortic valve repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
(85 reference statements)
0
16
0
Order By: Relevance
“…Beside the known low procedural risk and good clinical outcomes [ 1 8 , 10 , 13 , 14 ], the expectation of a superior quality of postoperative life might play a role in decision for aortic valve-sparing strategy. Hypothetically, better quality of life should result from the absence of anticoagulation and related life-style limitations, awareness of permanent risk of thromboembolic and bleeding complications, absence of blood checking and vigilance against prosthetic infection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beside the known low procedural risk and good clinical outcomes [ 1 8 , 10 , 13 , 14 ], the expectation of a superior quality of postoperative life might play a role in decision for aortic valve-sparing strategy. Hypothetically, better quality of life should result from the absence of anticoagulation and related life-style limitations, awareness of permanent risk of thromboembolic and bleeding complications, absence of blood checking and vigilance against prosthetic infection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean patient age ranged from 41 to 64 years, with an overall patient mean age of 45.3 years across all included studies. Within individual studies, however, age was more varied, with one study including patients ranging from 3 to 86 years15 and others including patients between 20 and 68 years of age 2021 The proportion of patients with aortic regurgitation was between 70% and 100% in all studies except for one 23.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests a considerably lower early mortality rate compared to a previous meta-analysis which did not focus exclusively on patients with BAVD (pooled estimated early mortality 0.026, 95% CI 0.014 to 0.044),6 potentially highlighting differences and the need for differentiations of patients with bicuspid versus tricuspid valves. However, two studies found no difference in long-term survival between the two valve types,20 22 although this might have been due to the rare occurrence of late deaths after the procedure. Our results confirm and extend the findings of another systematic review of 30, often small, aortic valve repair studies in BAVD patients which found a median 30-day mortality rate of 0% 7…”
Section: Discussionmentioning
confidence: 97%
“…The surgical technique has been previously described by our group [14]. Briefly, the geometric and effective height of the leaflets, presence of cusp prolapse, and the presence and location of degenerative changes, calcifications, and cusp fenestrations were analyzed in every valve.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Since Lansac and colleagues [12] introduced in 2005 the external aortic annuloplasty ring, the aortic root remodeling combined with the implantation of expansible annuloplasty ring evolved in the standardized physiologic approach to the valve-sparing root replacement [7]. This approach was adopted at our department in 2010 and has become the procedure of choice in patients with AR and root aneurysm [14]. Values are expressed as mean AE SD unless otherwise indicated.…”
Section: Commentmentioning
confidence: 99%